Influence of gel thickness on tooth bleaching efficacy (Research, Society and Development, 2022)
The aim of the study is to evaluate the influence of different thicknesses of bleaching gel on the efficacy of tooth bleaching. Seventy specimens in the form of standardized bovine enamel-dentin blocks were prepared, sequentially polished, and randomly divided into three groups, according to the bleaching agent used: CT (control-no bleaching; n=10) – Artificial saliva; HP (n=30) – 38% Hydrogen Peroxide and CP (n=30) – 10% Carbamide Peroxide. The HP and CP groups were divided into 3 subgroups according to the bleaching gel thickness: A – 0.5mm; B – 1.0mm and C – 2.0mm. The color was measured before and after (24 hours) of the bleaching treatment. Color difference (DE) and translucency (TP) were calculated. ΔE variations were statistically analyzed with two-way ANOVA. Translucency values were analyzed with the Student's T-test (p£0.05). Regarding, the DE and TP values, there were no significant differences between groups (p³0.05) for different thicknesses of bleaching gel. The thickness of the bleaching gel did not influence the effectiveness of bleaching, regardless of the bleaching agent used.